Embedded deformation of the rubble-mound foundation of gravity-type quay walls and influence factors - Zheng Qingsong (Open Geosciences, 2022)
In this study, the embedded depths of the rocks of the single-layer placement group and the multilayer riprap group were compared through a self-made test device. Besides, a finite element model of a single layer of regular rocks was developed to probe into the factors that impact the embedded deformation of the rubble-mound foundation of a gravity-type quay wall, including the cohesion and angle of internal friction of foundation soil, as well as the particle size of and the interval between rocks. Research results indicated that it was feasible to replace multilayer randomly dumped rocks with single-layer regularly placed rocks. The embedded depth decreased as the cohesion and angle of internal friction of soil increased. The influence of load on the embedded depth was small when the cohesion was less than 10 kPa or the angle of internal friction was smaller than 40°. When the load was lower than 80 kPa, the impact of the particle size of rocks on the embedded depth would be negligible, and such impact grew along with the load. When the load was below 100 kPa, the interval between rocks exerted relatively minor influence on the embedded depth: under a constant porosity, the embedded depth would decrease as the interval increased, and this correlation became more significant when the load exceeded 800 kPa; under varied porosities, a larger interval would lead to an increased embedded depth but the increase would be limited within a range of 10% of the original depth.